Proteostasis disruption under hypoxia: therapeutic targets in cancer and neurodegenerative diseases - Susi Rahmiyati; Ani Retno Prijanti; Sri Widia A Jusman; Syarifah Dewi (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Proteostasis, the integrated network regulating protein synthesis, folding, trafficking, and degradation, is essential for cellular function and organismal health. Reduced oxygen availability disrupts proteostasis through increased reactive oxygen species (ROS) production, endoplasmic reticulum (ER) stress, impaired ATP-dependent protein folding, and altered chaperone expression. In cancer, tumor cells exploit chronic unfolded protein response (UPR) signaling to enhance survival, angiogenesis, and therapeutic resistance. Inhibition of IRE1α and PERK pathways has shown efficacy in preclinical models, though clinical translation faces challenges including off-target toxicity. In neurodegenerative diseases—Alzheimer's, Parkinson's, and amyotrophic lateral sclerosis—chronic hypoxia accelerates protein aggregate accumulation through oxidative modifications and impaired autophagy-lysosome function. Therapeutic strategies targeting γ-secretase, BACE1, and protein clearance pathways have demonstrated limited clinical success despite mechanistic rationale. Understanding hypoxia-induced proteostasis failure may inform therapeutic development, though significant obstacles remain in translating preclinical findings to effective treatments for cancer and neurodegenerative diseases.